Work pressure in higher education: a state of the art bibliometric analysis on academic work–life balance - Muhammad Ashraf, Fauzi; Syed Radzi, Rahamaddulla; Lee, Chia Kuang; Zuraina, Ali; Umi Nabila, Alias (Emerald Publisher, 2024)
Purpose: The purpose of this study is to review the work–life balance (WLB) among academics. Academics are the pillars of higher education institutions’ (HEIs) mission to provide quality education to students and the community, supporting socioeconomic development. Most academics today are overworked and overburdened with duties, forcing them to work longer hours on weekends and at odd hours. This eventually affects their work–life balance and causes boundary conflicts between work and personal life. Design/methodology/approach: This study proposes a bibliometric analysis to investigate the underlying knowledge structure of this phenomenon by uncovering the past and present themes and predicting future trends of WLB in academia. This review adopts two analyses (bibliographic coupling and co-word analysis), presenting the knowledge structure network. A total of 307 journal publications were retrieved from the Web of Science (WoS) database, revealing significant clusters and themes. Findings: Findings identified central themes, including the issue of women in academia, predictors and the impact of WLB in academia. Research limitations/implications: Implications towards research and practice relevant to scholars and practitioners are discussed, particularly in balancing academics, professional work and personal life. Originality/value: This study presents a state-of-the-art bibliometric analysis by uncovering the knowledge structure of academics’ work–life balance in HEIs.